The Safety Policy Management Guidelines Based on Ariyasacca 4 of Schools at the Fifth Educational Network, Chatubhumi Srivijaya, Nakhon Si Thammarat Primary Educational Service Area Office 2: The Safety Policy Management Guidelines Based on Ariyasacca 4 of Schools at the Fifth Educational Network, Chatubhumi Srivijaya, Nakhon Si Thammarat Primary Educational Service Area Office 2 - Priksasri, Pongpan; Phrakhru Sumetpariyattikun; สามัคคี, ปรีชา (RATANABUTH JOURNAL, 2026)
This qualitative research aimed to (1) study existing safety policy management; (2) investigate safety administration guidelines based on the Four Noble Truths (Ariyasacca 4); and (3) propose and evaluate these guidelines. Data were collected from 15 in-depth interviews, five expert interviews, and a seven-specialist discussion, then analyzed using inductive analysis and focus group evaluation. Findings: 1) Existing policies include student care committees that reduce violence, accidents, and rights violations while improving safety and health awareness. 2) Guidelines enhance school awareness of privacy and safety, decreasing harassment and violations while creating a clean, caring, and efficient learning environment. 3) Specialists agreed that the Four Noble Truths-based guidelines were feasible, appropriate, and beneficial for school contexts.